Mathematics and Cosmology - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
The mathematical and cosmological works of a group associated with the Copernicus Center for Interdisciplinary Studies in Cracow are summarized. The group consists mainly of M. Heller, L. Pysiak, W. Sasin, Z. Odrzygóźdź and J. Gruszczak. The first paper by members of the group was published in 1988, and research has been continued to the present day. The main mathematical tool used in the first part of the group’s activity was the theory of differential spaces and, in the second, methods of noncommutative geometry. Among the main topics investigated have been classical singularities in relativistic cosmology and the unification of general relativity with quantum mechanics.